The Impact of Gender Inequality and Environmental Degradation on Human Well-being in the Case of Pakistan: A Time Series Analysis - Ali, Amjad; Audi, Marc; Bibi, Chan; Roussel, Yannick (International Journal of Economics and Financial Issues, 2021)
This study has investigated the impact of gender inequality and environmental degradation on human well-being in the case of Pakistan from 1980 to 2019. Augmented Dickey-Fuller unit root test is used for stationarity of the variables. The Autoregressive Distributed Lag Model (ARDL) is used for co-integration among the variables of the model. The results show that gender inequality has a negative and significant impact on human well-being in Pakistan, while gender equality encourages human well-being. The calculated results show that there is a positive, but insignificant relationship between environmental degradation and human well-being in the case of Pakistan. The estimated results show that economic misery has a negative and significant impact on human well-being in the case of Pakistan. The estimated results show that economic growth has a positive and significant relationship with human well-being in Pakistan. Based on estimated results, it is concluded that gender equality, economic misery, and economic growth are playing an important role in determining human well-being in Pakistan. Therefore, to improve human well-being, the government must reduce gender inequality and economic misery while enhancing in parallel economic growth. Keywords: gender inequality, environmental degradation, human well-being JEL Classifications: J1, O10, Q0 DOI: https://doi.org/10.32479/ijefi.8415